Study on Impact of Marble Dust on a Cement Concrete as a Partial Replacement (International Journal of Innovative Research in Engineering & Management, 2023)
A product of the marble-making process  is marble dust. The cutting process produces a significant  amount of powder. Consequently, about 25% of the  original marble mass is lost to dust. Directly discharging  these waste products into the environment could lead to  environmental issues including increased soil alkalinity,  negative impacts on plants and people's health, etc.  Concrete can be strengthened by adding marble powder as  an addition. It is a stable byproduct of the manufacture of  marble that can be used as a cement filler or as fine  aggregates in concrete. Concrete that is built using this  debris is more affordable and long-lasting, which can assist  to address a number of ecological and environmental  problems. This study explores the practicality of using  marble waste in place of cement to conserve resources and  the environment. This study examines the substitution of  fine aggregate in concrete with marble dust particles. At  content levels of 0, 4, 8, 12, and 16, marble has taken the  place of fine aggregate in concrete. Five different series of  concrete mixtures were made in order to evaluate the  various characteristics of marble dust concrete. Controlled  concrete's workability, compressive strength, water  absorption, specific gravity, and other characteristics have  all been compared.
Keywords: Sieve Analysis; Marble Dust; Slump Cone Test; Compressive Strength Test; plit Tensile Strength Test